Hubungan Koordinasi Mata Tangan Dan Kekuatan Otot Lengan Terhadap Kemampuan Servis Panjang Dalam Permainan Bulutangkis Siswa Tunarungu SLB Negeri Mimika - Habibi Sutirta; Sukmah Sukmah; Ivan Lavandi (Riyadhoh : Jurnal Pendidikan Olahraga, 2022)
This study aims, among others, (1) to determine the relationship of eye-hand coordination to the accuracy of long serve in badminton games in Mimika State Special School students. (2) To determine the relationship between arm muscle strength and long serve accuracy in badminton games for Mimika State Special School students. (3) To determine the relationship between hand eye coordination and arm muscle strength on long serve ability in badminton games for Mimika State Special School students. This type of research is descriptive correlation research. The sample in this study was 15 students with disabilities SLB Mimika State. The data analysis technique used is correlation and regression analysis technique using the SPSS Version 22 system at a significant level of 95% or 0.05. The results of data analysis show that: (1) the value of rcount = 0.699 > rtable(0.05)(15) = 0.514, thus it is concluded that there is a significant relationship between hand eye coordination and long serve ability in badminton games for Tunarung SLB Mimika students ( 2) the value of rcount = 0,540 > rtable(0.05)(15) = 0,514, thus it can be concluded that there is a significant relationship between arm muscle strength and long serve ability in badminton in deaf students at the Mimika State Special School. (3) Test the significance of the coefficients obtained by the value of Fcount 7.54 > Ftable 3.89 at a significance level of 0.05 and Rcount = 0.700 > Rtable(0.05)(15) = 0.514, thus it can be concluded that there is a significant relationship between eye coordination hand and arm muscle strength on the accuracy of long serve in badminton for Mimika State Special School students.